A Motion-based User Interface for the Control of Virtual Humans Performing Sports - Liang, Xiubo; Wang, Zhen; Geng, Weidong; Multon, Franck (International Journal of Virtual Reality, 2011)
Traditional human computer interfaces are not intuitive and natural for the choreography of human motions in the field of VR and video games. In this paper we present a novel approach to control virtual humans performing sports with a motion-based user interface. The process begins by asking the user to draw some gestures in the air with a Wii Remote. The system then recognizes the gestures with pre-trained hidden Markov models. Finally, the recognized gestures are employed to choreograph the simulated sport motions of a virtual human. The average recognition rate of the recognition algorithm is more than 90% on our test set of 20 gestures. Results on the interactive simulation of several kinds of sport motions are given to show the efficiency and interestingness of our system, which is easy-to-use especially for novice users